THE APPLICATION OF COMBINED TIME SERIES MODELING AND MINIMUM DISTANCE METHOD IN IDENTIFYING UNBALANCE AND MECHANICAL LOOSENESS FAULTS IN ROTATING MACHINERIES - TIONO DECCA SAKTI (NIM : 13105142 ) Pembimbing : Ir. Ign. Pulung Nurprasetio, MSME, YANG
This undergraduate thesis focus is on the application of condition based maintenance or CBM. CBM is basically a maintenance scheme in which the decision to repair machineries will be determined based on the monitoring results of the condition of the machines. Specifically, in this undergraduate thesis, the monitoring is performed by measuring the vibration level of the machines. In order to perform the diagnosis, a combined method based on time-series modeling and minimum distance is employed [Dianviviyanthi and Nurprasetio, 2000]. The main objective of this research work is to implement the above method in identifying unbalance fault and also mechanical looseness in rotating machineries. To see the effectiveness of the method, a test rig consisting of a simply supported continuous beam with an unbalance exciter is used in the laboratory experiment. The test rig is available at the Mechanics and Mechanical Construction Laboratory. In order to introduce mechanical looseness, additional gap is provided in one of the clamping support of the beam. Data analysis shows that the method correctly identifies the simulated fault conditions, in the sense that it is able to accurately detect unbalance fault and the combination of unbalance and mechanical looseness. Based on the above, further investigation to see the reliability of the method is proposed as a continuation of this undergraduate thesis.